RESPONS DOKTER DAN KESIAPAN PEMANGKU KEPENTINGAN DALAM IMPLEMENTASI UNDANG UNDANG PRAKTIK KEDOKTERAN DI KOTA MEDAN - , ZULFENDRI, DRS.,M.KES. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The implementation of Law No. 29/2004 on Medical Practice (LMP) that involves many stakeholders need to be assessed in order to improve the policy and health system. This study aims to assess the implementation of LMP in Medan in 2007 â 2012, through doctors response on the Law and throught stakeholder preparedness to implement the law. This study employs a mixed method. Results: 10 years after the launch of LMP, doctors have shown good faith to accept and implement. Good faith is based on the majority of that 60% (6 of 10 Variable Response) has responded to â¥ in both categories by a doctor, except on legal sanctions and the role played by law enforcement and NGOs as environmental factors. Ministry of Health, as part of its function, duty and jurisdiction, have succeeded in designing regulation on medical practice, through Minister of Health (MOH) Decree and the MOH Act. The Indonesian Medical Council (IMC) and the Indonesian Honorary Council for Medical Disciplinary (IHCMD) as part of its function, duty and jurisdiction internally regulated medical practice through IMC regulation and IMC act, administer doctor registration and establish educational standard for medical profession. IHCMD has enforced doctor and dentist to comply to Case Management of Doctor Dentist Disciplinary Violation. However, the level of implementation of this enforcement has not been considered proactive. MOH and IMC have not intensively employed their advisory and monitoring roles on the management of medical practice. District level health office, as part of its function, duty and jurisdiction has issued registration for medical practice, record and map medical practices in its territory. However, again, its advisory and monitoring roles have not been intensively explored. In addition, district level regulation on medical practice has still not been established. In accordance to the LMP, associations of medical profession (Indonesian Doctoral Association/Indonesian Dentists Association) in Medan provide advice, conduct monitoring and enforce medical ethics. There are still gaps in perception between medical community and law enforcer regarding enforcement process of criminal law for medical practice. Multiple regression showed that doctorâs response to LMP missions is associated with doctorâs compliance to LMP (p<0.05, adj R-square=0.5173). Doctorâs response to penalty has the strongest association compared to other variables (Ã = 0,68). Conclusion: Doctorâs response to LMP missions is associated with his/her compliance to the law. Stakeholders are not well prepared to implement LMP. LMP needs to be revised in order to manage its implementation by health care system. Keywords: doctorâs response, stakeholderâs preparedness, implementation of the Law of Medical Practice